2003
DOI: 10.1177/142032603035546
|View full text |Cite
|
Sign up to set email alerts
|

Determining Domestic Formaldehyde Levels in Ankara, Turkey

Abstract: This cross-sectional study was carried out in October, 2001, with the aim of measuring formaldehyde levels in 399 homes representative of those in the central districts of Ankara province. Measurements were carried out with a Formaldemeter 400 in the living rooms and kitchens of these homes. The average formaldehyde levels in living rooms and kitchens were 0.064 and 0.060 ppm, respectively. The correlations between formaldehyde levels and type of house, construction materials, and method of ventilation were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
4
1
6
Order By: Relevance
“…The formaldehyde concentrations measured in this study were in the literature range (10-400 g/m 3 , Daisey et al, 2003). The concentrations measured in this study were higher than those reported for schools in other countries (Sweden, Norback et al, 1990;Smedje et al, 1997;Hong Kong, Lee et al, 2002;Australia, Zhang et al, 2006), while they were lower than the concentrations measured in homes and offices (Vaizoglu et al, 2003;Khoder, 2006;Mentese and Gullu, 2006;Park and Ikeda, 2006), and were similar to those in libraries (Hanoune et al, 2006;Righi et al, 2002).…”
Section: Classroomsupporting
confidence: 45%
“…The formaldehyde concentrations measured in this study were in the literature range (10-400 g/m 3 , Daisey et al, 2003). The concentrations measured in this study were higher than those reported for schools in other countries (Sweden, Norback et al, 1990;Smedje et al, 1997;Hong Kong, Lee et al, 2002;Australia, Zhang et al, 2006), while they were lower than the concentrations measured in homes and offices (Vaizoglu et al, 2003;Khoder, 2006;Mentese and Gullu, 2006;Park and Ikeda, 2006), and were similar to those in libraries (Hanoune et al, 2006;Righi et al, 2002).…”
Section: Classroomsupporting
confidence: 45%
“…En estudios internacionales la calidad de la ventilación se ha evaluado tomando en cuenta la ventilación natural (Báez et al 2003, Zhao et al 2004) y los aparatos para dicha ventilación (Vaizoglu et al 2003, Park e Ikeda 2006. En países fríos han medido la concentración de dióxido de carbono como indicador de una ventilación deficiente (Dally et al 1981), o utilizado gas traza para medir la tasa de renovación de aire/hora (Gilbert et al 2006).…”
Section: Discussionunclassified
“…Resultados de la evaluación del efecto de la ventilación natural sobre la concentración de formaldehído pueden ser diferentes e incluso controversiales para una misma localidad y vivienda (Vaizoglu et al 2003). La mayoría han reportado asociación entre una mejor ventilación y una menor concentración (Zhao et al 2004, Gilbert et al 2006, Heroux et al 2010, Hullin et al 2010, Brown et al 2015.…”
Section: Discussionunclassified
See 2 more Smart Citations